PREVALENCE AND RISK FACTORS OF PSYCHOTRAUMA AMONG INCARCERATED MALE JUVENILES - Prasetyo Aji Nugroho; Uji Kawuryan; Maulana Bakir; Desmalia Nurhidayah (NurseLine Journal, 2025)
Background: Understanding the prevalence and correlates of psychotrauma in this population is crucial for developing trauma-informed interventions within correctional facilities. Objective: to determine the prevalence of psychotrauma and its association with socio-demographic and risk factors among incarcerated male juveniles in West Borneo, Indonesia. Methods: A cross-sectional descriptive design involving 57 male juveniles recruited through a total sampling approach. Data were collected using Global Psychotrauma Screen-Teen Version. Results: Most respondents were aged 16-17 years (68.4%), single (96.4%), Muslim (77.2%), unemployed prior to incarceration (70.2%). Nearly half were convicted of sexual crimes (45.6%), smoking was the most common pre-incarceration misbehavior (47.4%). Screening indicated that 29.8% of juveniles experienced psychotrauma, while 70.2% did not. Bivariate analysis revealed a significant association between living arrangements and psychotrauma (p=0.041), with juveniles not residing with their families before incarceration being more vulnerable. Conclusion: Nearly one-third of incarcerated male juveniles screened positive for psychotrauma, with family context emerging as an important factor. These findings underscore need for universal trauma screening and trauma-informed care in juvenile justice settings to improve mental health outcomes and reduce recidivism. High proportion of sexual offenses suggests a potential link between early victimization and later delinquent behavior, supporting need for trauma-informed rehabilitation programs.